2021
DOI: 10.5194/hess-2021-433
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trends and variability in snowmelt in China under climate change

Abstract: Abstract. Snowmelt is a major fresh water resource, and quantifying snowmelt and its variability under climate change is necessary for planning and management of water resources. Spatiotemporal changes in snow properties in China have drawn wide attention in recent decades; however, country-wide assessments of snowmelt are lacking. Using precipitation and temperature data with a high spatial resolution (0.5 seconds, approximately 1 km), this study calculated the monthly snowmelt in China for the 1951–2017 peri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Based on high spatial resolution precipitation and temperature data, Yang et al (2022a) produced a monthly snowmelt dataset for China (SMT-Y) using a simple temperature index model. Because snowmelt is difficult to measure directly, the calculated snowmelt was verified using snowfall, snow depth, snow cover extent and snow water equivalent data, which indicated that is reliable (Yang et al, 2022b).…”
Section: Monthly Snowmelt Dataset In Chinamentioning
confidence: 99%
“…Based on high spatial resolution precipitation and temperature data, Yang et al (2022a) produced a monthly snowmelt dataset for China (SMT-Y) using a simple temperature index model. Because snowmelt is difficult to measure directly, the calculated snowmelt was verified using snowfall, snow depth, snow cover extent and snow water equivalent data, which indicated that is reliable (Yang et al, 2022b).…”
Section: Monthly Snowmelt Dataset In Chinamentioning
confidence: 99%
“…Aarts et al [28], An and Wang [29], Bastian et al [30], Cao et al [31], Chen and Zhao [32], Chen et al [33], Dang [34], Dantsis et al [35], Deng et al [36], Ding [37], Ding et al [38], Hu [39], Li [40], Li and Wang [41], Li et al [42], Lin [43], Liu [44] [63], Wang [64], Wang [65], Wang and Gorobets [66], Wang and Lan [67], Wang and Wang [68], Wang and Yang [69], Wang et al. [70], Wang et al [71], Wang et al [72], Wang et al [73], Wu and Du [74], Xu [75], Yang [76], Yao [77], Yao and Zhang [78], Yu [79], Zhang [80], Zhang and Cao [81], Zhang and Gou [82], Zhang and Zhu [83], Zhang et al [84], Zhang et al [85], Zhao [86], Zhao [87], Zhao et al [88], Zhou [89],…”
Section: Regional Levelmentioning
confidence: 99%